The Promise of a Managerial Values Approach to Corporate Philanthropy - CHOI, Jaepil (Institutional Knowledge at Singapore Management University, 2007)
This article presents an alternative rationale for corporate philanthropy based on managerial values of benevolence and integrity. On the one hand, top managers with benevolence and integrity values are more likely to spread their intrinsic concern for others into the wider society in the form of corporate philanthropy. On the other hand, top managers high in benevolence and integrity are likely to contribute to improved managerial credibility and trusting firm-stakeholder relationships, thereby improving corporate financial performance. Therefore, the article makes the argument that both corporate philanthropy and corporate financial performance can better be interpreted as resulting from managers’ benevolence and integrity values.